NSRRC Holds Dedication Ceremony for the Taiwan Photon Source's New Experimental Facility. Issue 6 (1st November 2016) - Lin, Diana
Abstract : More than 300 participants, including nearly 50 invited guests, attended the dedication ceremony for the Taiwan Photon Source's (TPS) new experimental facility at the National Synchrotron Radiation Research Center (NSRRC) on September 19, 2016. The special ceremony marked an important milestone that will dramatically change the course of Taiwan's scientific advancement in the coming years. Since the successful commissioning of the synchrotron accelerator TPS on New Year's Eve in 2015, the NSRRC has constructed an additional seven beamlines during Phase I of the TPS Experimental Facility Construction Project in order to channel an electron beam of 3 billion electron volts (GeV) away from the circular TPS storage ring into the experimental target samples. The ceremony, inaugurated by President Ing-Wen Tsai, officially announced the availability of these beamlines to scientific users worldwide.